Healthcare worker compliance with seasonal and pandemic influenza vaccination - Bellia, Claire (Influenza Other Respir Viruses, 2013)
Healthcare workers (HCWs) can be an important source of transmission of influenza to patients and family members, and their well‐being is fundamental to the maintenance of healthcare services during influenza outbreaks and pandemics. Unfortunately, studies have shown consistently low levels of compliance with influenza vaccination among HCWs, a finding that became particularly pronounced during recent pandemic vaccination campaigns. Among the variables associated with vaccine acceptance in this group are demographic factors, fears and concerns over vaccine safety and efficacy, perceptions of risk and personal vulnerability, past vaccination behaviours and experience with influenza illness, as well as certain situational and organisational constructs. We report the findings of a review of the literature on these factors and highlight some important challenges in interpreting the data. In particular, we point out the need for longitudinal study designs, as well as focused research and interventions that are adapted to the most resistant HCW groups. Multi‐pronged strategies are an important step forward in ensuring that future influenza vaccination campaigns, whether directed at seasonal or pandemic strains, will be successful in ensuring broad coverage among HCWs.